On the modulus of continuity of solid derivatives of a Cauchy-type integral - Gerus, O. F. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We establish sufficient conditions for the existence of solid derivatives of a continuous extension of a Cauchy-type integral onto the closure of a domain and obtain an estimate for the moduli of continuity of these derivatives. We prove that the Newton-Leibniz formula is true for certain classes of Jordan rectifiable curves.